Phosphine induced Nickel Migration in SOFC Anodes: A Computational Study. (10th February 2015) - Sezer, Hayri; Celik, Ismail B.
Abstract: The poisoning of anode materials by impurities in coal syngas is a significant problem for utilization of coal syngas in Solid Oxide Fuel Cells (SOFCs). One such impurity, phosphine is known to cause catastrophic failure of SOFC anode at ppm level concentrations. A significant phenomenon observed in SOFC anodes, made of Ni-YSZ cermets, when exposed to phosphine is migration of the nickel from porous matrix towards the surface, which is believed to be one of the reasons for performance degradation. The mechanisms responsible for the experimentally observed nickel migration are not well understood. In this study, a plausible mechanism is proposed to reveal the effect of electrical current and steam concentration on nickel migration in SOFC anodes. A physics based transport model for nickel migration is formulated based on the electro-migration, formation of the secondary phases and diffusion. This model is integrated into a readily available one dimensional in house code for predicting SOFC anode degradation due to fuel impurities. Simulations show that the proposed mechanism of Ni diffusion driven by secondary phase formation, the electrical force, and humidity can reveal the experimentally observed accumulation of Ni and secondary phases on the SOFC anode surface.